ANALISIS PENGAMBILAN KEPUTUSAN TERHADAP KEPUASAN PELANGGAN KFC DI KOTA BATAM DENGAN METODE SIMPLE ADDITIVE WEIGHTING - Candra Pranata; Muhammat Rasid Ridho (Computer Science and Industrial Engineering, 2025)
Customer satisfaction assessment is a crucial aspect for fast food company. This study aims to analyze customer satisfaction levels at KFC Gelael, Palm Spring Batam using the Simple Additive Weighting (SAW) method. The research identifies five key criteria: product quality, cleanliness, service, price, and atmosphere. Data were collected through online questionnaires distributed to 100 respondents who had visited KFC Gelael, Palm Spring Batam. The analytical stages include deretmining cost and benefits attributes, decision matrix formulation, data normalization, criteria weighting, and ranking using the SAW method. The results show that most customers rated KFC’s services as satisfactory, with the highest SAW score reaching 0.967. in conclusion, the SAW method proves effective in supporting decision-making based on customer satisfaction priorities and can serve as a strategic cconsideration for KFC management in improving customer satisfaction.